Iodine value analysis on RBD palm olein and RBD palm stearin - Lestari, Puji; Yusuf, Faisal; Furqan, Mainal (Journal of Midwifery and Nursing, 2025)
Studies and analyses were made to determine the degree of uncertainty in the iodine value estimation of refined, bleached, and deodorized (RBD) palm oil and after fractination (RBD palm olein and RBD palm stearin). At refining process and produce Refined Bleached Deodorized Palm Oil (RBDPO), enter the fractionation process will produce RBD palm olein (RBDPL) and RBD palm stearin (RBDPS). A commonly used metric to assess the quality of vegetable oils is the iodine value (IV).  The main objective is to observe IV of RBDPL and RBDPS after fractination process. The approved AOCS Cd 1–25 technique was used to compute this parameter. The IV of the RBDPO samples shows that RBDPL and RBD PS met the requirement specified by PORAM with a iodine value of RBDPO is 52.33°C–53.06°C for RBDPO (standard 50-55), RBDPL is 58.13 – 58.40 (standard min 56) and RBDPS is 34.18 – 35.81 (standard 48 max).